Identifikasi Gaya Belajar ditinjau dari Kecenderungan Bakat Khusus pada Mahasiswa Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Metro - Agus Wibowo; Nurul Atieka (Universitas Mathla'ul Anwar Banten, 2019)
IDENTIFICATION OF LEARNING STYLES BASED FROM SPECIAL TALENT STUDENT PROGRAM STUDY OF GUIDANCE AND COUNSELING UM METRO. Pragmatism of educational practice can be seen from learning process without based of individual characteristics. This condition appears in the selection of methods and strategies of lstudents who tend to be oriented towards teacher oriented. In learning identification the characteristics of students are very poorly identified by teachers. Based from the problems, it is very important to study and identify student talents and student learning styles. Through this research, it is expected to be a reference in the development of the learning process based of special talents and student learning styles. This study aims to identify the characteristics of talent, learning styles, and the relationship between talent and learning styles in students. The method used is correlational research. Data collection uses aptitude tests and learning style scales.The results of research is majority students guidance and counseling study program of UM Metro have special talent is vebal talent, dan characteristics of style learning is visual learning. Thus the results of the study also show that the majority of students who have a verbal talent are also types of visual learning.